1973
DOI: 10.1159/000211982
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Aging in Hypopituitary Dwarf Mice

Abstract: Changes occurring in lumbar and lower thoracic vertebrae of aging dwarf mice (dwdw) were compared with those found in non-dwarfs of the same strain (Dwdw or DwDw) and of strain C57B1. Dwarf vertebrae, besides remaining smaller, develop less completely and more slowly than those of non-dwarfs. Retarded development is indicated by the presence of non-resorbed epiphyseal cartilage, by diminished removal of cancellous bone from the vertebral bodies and possibly also by the failure of osseous replacement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1974
1974
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 6 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…The present findings are similar to those in the vertebrae of hypopituitary dwarf mice. in which all phases of skeletal growth and development are retarded [12].…”
Section: Discussionmentioning
confidence: 99%
“…The present findings are similar to those in the vertebrae of hypopituitary dwarf mice. in which all phases of skeletal growth and development are retarded [12].…”
Section: Discussionmentioning
confidence: 99%
“…First reports of data concerning aging and longevity of hypopituitary dwarf mice lacking somatotrophs appeared in the 1970s, but the findings were contradictory with the observed lifespans being drastically reduced [39], not reduced [40] or impressively extended [41, 42]. Subsequent studies in a different mutant with the same endocrine phenotype [20] and reexamination of the longevity of mutants that had been studied in the 1970s [21], demonstrated that combined deficiency of GH, thyrotropin and prolactin in both Ames dwarf (Prop1 df ) and Snell dwarf (Pit1 dw ) mice is associated with significant, very pronounced (approximately 30 – 70%, depending on sex and diet) extension of longevity [20, reviewed in 43, 44].…”
Section: Evidence That Gh Can Accelerate Agingmentioning
confidence: 99%
“…The present findings give qualified support to the view stressing the cartilaginous origin of the osteophytes [7,12] as opposed to the hypothesis attributing them to mem branous ossification at the fibrous insertion of the annulus fibrosus at the vertebral margin [12], Proliferation of chondrocytes may be triggered by mechanical irritation following nuclear prolapse and subsequent mal alignment of the opposing vertebrae. In the absence of damage to the disc, systemic influences may come into play, as suggested by Schmorl and J unghanns [12] and G loobe and Nathan [8] and demonstrated in cases of acromegaly [6], and by the attenuation of spondylosis in hypopituitary dwarf mice [17].…”
Section: Discussionmentioning
confidence: 99%